Faktor Penyebab Gangguan Jiwa pada Klien di Poli Jiwa RSJ Kalawa Atei Provinsi Kalimantan Tengah - Missesa Missesa Missesa (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2021)
Abstract – Severe mental disorder in Central Kalimantan Province is 0.9 per mile, where the area is quite large and has not been categorized as a metropolitan city. The emergence of mental problems is certainly a concern, although not much but has a broad impact on various aspects of life, indirectly affecting regional development. Was to determine the causative factors associated with mental disorders in clients who were at the Mental Polyclinic of the Kalawa Atei Hospital, Central Kalimantan. This research is expected to have benefits by knowing the causative factors so that efforts can be made as early as possible to prevent or experience mental disorders. Is descriptive design with a sample of 97 respondents. Data collection strategies were interviews with questionnaires and physical examinations. This research pays attention to the ethical principles of research. The results showed that the biological factors causing mental disorders with a high percentage were history of non-exclusive breastfeeding and not drinking breast milk 64.3%, drug consumption 30.9%, heredity 12.4%, physical illness 4.1%, abnormal nutrition 2 .1%; factors that cause mental disorders are 93.8% introvert experience and 26.8% unpleasant experience; and socio-cultural factors, namely male sex 75.3%, not having a partner 71.1%, not/rarely practicing worship 63.9%, low education 63.9%, less income and no income 51.8%, 50.5% authoritarian parenting, 44.3% not working, and 9.3% of household conflicts. The recommendation of this research is that nurses make efforts to detect mental disorders in the community early by reflecting on the causes that are at risk for the occurrence of mental disorders.